2017
DOI: 10.1098/rsta.2017.0037
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature atomic layer deposition of SiO 2 /Al 2 O 3 multilayer structures constructed on self-standing films of cellulose nanofibrils

Abstract: In this paper, we have optimized a low-temperature atomic layer deposition (ALD) of SiO 2 using AP-LTO® 330 and ozone (O 3 ) as precursors, and demonstrated its suitability to surface-modify temperature-sensitive bio-based films of cellulose nanofibrils (CNFs). The lowest temperature for the thermal ALD process was 80°C when the silicon precursor residence time was increased by the stop-flow mode. The SiO 2 film deposition rate was depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…The ALD technique is widely used in many important industrial applications (e.g., protective coatings, microelectronics, photovoltaics, and solid oxide fuel cells) [ 86 ]. Studies have shown that ALD can be successfully employed to impart functional coatings of metal oxides and metal nitrides onto different types of cellulose based substrates such as cotton fibers [ 87 , 88 ], viscose fibers [ 88 ], and nanocellulose films [ 89 ].…”
Section: Surface Modificationmentioning
confidence: 99%
“…The ALD technique is widely used in many important industrial applications (e.g., protective coatings, microelectronics, photovoltaics, and solid oxide fuel cells) [ 86 ]. Studies have shown that ALD can be successfully employed to impart functional coatings of metal oxides and metal nitrides onto different types of cellulose based substrates such as cotton fibers [ 87 , 88 ], viscose fibers [ 88 ], and nanocellulose films [ 89 ].…”
Section: Surface Modificationmentioning
confidence: 99%
“…Overall, the incorporation of nanocellulose in an inorganic structure for efficient manipulation of the thermal properties in the final hybrid composite, has been analytically described (Nie et al 2020a, b;Zhang et al 2020Zhang et al , 2019. Previously, we have optimized the low temperature ALD multilayer deposition process on nanocellulose for the control over oxygen and water vapor transmission rates (Putkonen et al 2017). The employment of nanocellulose for fabrication of energy-related hybrid inorganic-organic systems, however, still exhibits plenty of space to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Los compuestos químicos liberados a la atmósfera se disocian formando iones, que al interactuar con la superficie del acero alcanzan potenciales de oxidación de 0.68V y 0.51V para Cl -, SO2 respectivamente [4,5]. Los mecanismos de protección de este tipo de metales se han usado desde el siglo XIX con protecciones del tipo físico en forma de barrera [6][7][8] y químico cuando el otro material se sacrifica para evitar el deterioro de la estructura [9][10][11]. Sin embargo, con los altos índices de contaminación y el incremento de la emisión de los gases de efecto invernadero, la tendencia en innovaciones a proteger estos metales se sigue incrementando.…”
Section: Introductionunclassified